Implementasi Program Shalat Berjamaah dalam Membentuk Kesadaran Beribadah Siswa di MTs Yapdi Medan - Dewi Aryanti; Ihsan Satria Azhar (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the implementation of the congregational prayer program in fostering students’ worship awareness at MTs Yapdi Medan, identify the challenges encountered during its implementation, and formulate appropriate solutions. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings show that the congregational prayer program effectively cultivates students’ worship awareness through habituation, teachers’ role modeling, and support from both the school and parents. The challenges identified include students’ limited understanding of congregational prayer, as reflected in behaviors such as joking during prayer or delaying it. The solutions implemented involve intensive supervision by teachers, socialization of the importance of congregational prayer during morning assemblies, and parental involvement in monitoring students’ worship practices at home. The novelty of this study lies in its empirical focus at the MTs level, emphasizing the direct relationship between the implementation of congregational prayer programs and the development of students’ worship awareness.